U-shaped association between serum albumin and pediatric intensive care unit mortality in critically ill children - Xuepeng Zhang; Xuepeng Zhang; Xuepeng Zhang; Lifan Zhang; Canzheng Wei; Canzheng Wei; Liwei Feng; Juqin Yang; Geng Zhang; Guoyan Lu; Xiying Gui; Yue Zhou; et al. (Frontiers in Nutrition, 2022)
IntroductionThe detailed association between albumin levels and mortality has not been studied in critically ill children. The aim of this study was to reveal an association between albumin levels in detail and mortality in critically ill children.Materials and methodsWe retrospectively collected data from children admitted to four pediatric intensive care units (PICUs) in China between January 2015 and October 2020. Restricted cubic spline curves based on logistic regression models were generated to evaluate the detailed associations between serum albumin levels and PICU mortality. Threshold effect analysis was performed using two piecewise regression models.ResultsThe study included 9,123 children. The overall mortality was 5.3%. The detailed association between serum albumin levels and the risk of mortality followed a U-shape. The risk of mortality decreased with increasing serum albumin levels (OR = 0.919; 95% CI: 0.886, 0.954) in children with serum albumin levels < 43.2 g/L and increased with increasing serum albumin levels (OR = 1.174; 95% CI: 1.044, 1.316) in children with serum albumin levels ≥ 43.2 g/L.ConclusionThere was a U-shaped association between serum albumin levels and mortality in critically ill children in the PICU.